2021
DOI: 10.1101/2021.06.10.447924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective sweeps influence diversity over large regions of the mouse genome

Abstract: To what extent do substitutions in protein-coding versus gene-regulatory regions contribute to fitness change over time? Answering this question requires estimates of the extent of selection acting on beneficial mutations in the two classes of sites. New mutations that have advantageous or deleterious fitness effects can induce selective sweeps and background selection, respectively, causing variation in the level of neutral genetic diversity along the genome. In this study, we analyse the profiles of genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
(137 reference statements)
0
5
1
Order By: Relevance
“…How do our estimates in M. m. castaneus compare to those obtained using LDHelmet and a CO-only recombination model? Coestimated under a model of GC, our genome-wide average of the CO rate per-base (0.00186) is approximately 5 times lower than the ρ estimates obtained by Booker et al (2017 , 2021) using LDhelmet (0.00924 and 0.0100, respectively, averaged across autosomes). If we instead compare the total recombination rate between any 2 adjacent bases, which corresponds to the upper bound of the recombination rate in our model (for d = 1 eq.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…How do our estimates in M. m. castaneus compare to those obtained using LDHelmet and a CO-only recombination model? Coestimated under a model of GC, our genome-wide average of the CO rate per-base (0.00186) is approximately 5 times lower than the ρ estimates obtained by Booker et al (2017 , 2021) using LDhelmet (0.00924 and 0.0100, respectively, averaged across autosomes). If we instead compare the total recombination rate between any 2 adjacent bases, which corresponds to the upper bound of the recombination rate in our model (for d = 1 eq.…”
Section: Discussioncontrasting
confidence: 62%
“…The data—originally described in Halligan et al (2010) (ENA accession number PRJEB2176)—consists of Illumina (PE) resequence data for 10 individuals sampled from a wild M. m. castaneus population in India. Variant calling is described in Booker et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of house mice to rapidly adapt to these new conditions was paramount to their successful global colonization. Although prior studies have identified genome-wide targets of positive selection in house mice (Staubach, et al 2012; Phifer-Rixey, et al 2018; Booker, et al 2021; Lawal, et al 2021), focus has been mostly restricted to the discovery of selection on new mutations, rather than selection on standing variation. The waiting time to new adaptive mutations may be substantial, implying that adaptation may often be driven by selection on standing variants (Duvaux, et al 2011; Reid, et al 2016; Lai, et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the impact of positive selection, in which beneficial alleles are favored by selection and thus increase in frequency in the population, is hotly debated [1][2][3]. This controversy extends to the role of selective sweeps [4], in which positively selected mutations rapidly sweep through a population thereby drastically reducing and altering patterns of genetic diversity in the vicinity of the selected locus [5,6], with some studies finding that signatures of selective sweeps alter genome-wide patterns of polymorphism [7][8][9][10][11] , and others purporting that these signatures may be largely or even entirely false positives [12].…”
Section: Introductionmentioning
confidence: 99%